Umbelliferone induces changes in the structure and pharmacological activities of Bn IV, a phospholipase A(2) isoform isolated from Bothrops neuwiedi - Toyama, Daniela de Oliveira; dos Santos Diz Filho, Eduardo Britto [UNESP]; Cavada, Benildo Sousa; Matias da Rocha, Bruno Anderson; Buzzo de Oliveira, Simone Cristina [UNESP]; Cotrim, Camila Aparecida [UNESP]; Gomes Soares, Veronica Cristina [UNESP]; Delatorre, Plinio; Marangoni, Sergio; Toyama, Marcos Hikari [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
In this paper was demonstrated that umbelliferone induces changes in structure and pharmacological activities of Bn IV, a lysine 49 secretory phospholipase A(2) (sPLA2) from Both tops neuwiedi. Incubation of Bn IV with umbelliferone virtually abolished platelet aggregation, edema, and myotoxicity induced by native Bn IV. The amino acid sequence of Bn IV showed high sequence similarities with other Lys49 sPLA2s from B. jararacussu (BthTx-I), B. pirajai (PrTx-I), and B. neuwiedi pauloensis (Bn SP6 and Bn SP7). This sPLA2 also has a highly conserved C-terminal amino acid sequence, which has been shown as important for the pharmacological activities of Lys49 sPLA2. Sequencing of Bn IV previously treated with umbelliferone revealed modification of S(1) and S(20). Fluorescent spectral analysis and circular dichroism (CD) studies showed that umbelliferone modified the secondary structure of this protein. Moreover, the pharmacological activity of Bn IV is driven by synergism of the C-terminal region with the a-helix motifs, which are involved in substrate binding of the Asp49 and Lys49 residues of 5PLA2 and have a direct effect on the Ca2+-independent membrane damage of some secretory snake venom PLA2. For Bn IV, these interactions are potentially important for triggering the pharmacological activity of this 5PLA2. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Secretory phospholipase A(2) (sPLA2); Lys49 PLA2; Umbelliferone; Anti-PLA2 activity